Scaling drought tolerant rice varieties and alternate wetting and drying in the Niger Office zone - Sidibe, Mahamadou; Dossou-Yovo, E. R. (2024)
Rice farming in Mali is a critical component of food security and rural livelihoods, yet it faces significant challenges due to water scarcity, recurrent droughts, and the impacts of climate change. This report highlights the outcomes of a collaborative initiative between the AICCRA project and the Niger Office to scale drought-tolerant rice varieties and Alternate Wetting and Drying (AWD) practices. Through pilot projects, capacity-building efforts, and farmer-centric approaches, the initiative successfully reached over 38,500 farmers including 14,245 women in 31 sites. These efforts led to a 20-30% increase in yields, 25-35% water savings, and a 15-20% reduction in production costs, significantly enhancing productivity, water use efficiency, and climate resilience. Key lessons, challenges, and recommendations for further scaling are also outlined, providing a pathway for sustainable rice production in Mali.